Un análisis de los procesos de deslocalización productiva: inversión extranjera directa e importación de bienes intermedios en la Industria Vasca - RODRÍGUEZ GONZÁLEZ, Carlos; BUSTILLO MESANZA, Ricardo (Cuadernos de Relaciones Laborales, 2010)
The offshoring is a phenomenon which causes an increasing concern in the Basque Country. The developing countries’ share over total FDI, as well as the intermediate products’ share over world intermediate imports have both increased throughout the last decade. There is a geographical and branch correspondence between FDI and trade flows for some sectors (Metal, Food and beverages), a fact that shows that the chosen strategy to reduce labour costs has been the vertical FDI and intra-firm trade. In other branches like Chemical Products there is no correspondence, what remarks the international outsourcing choice, taking place between independent companies. The negative consequences of offshoring over local employment should be removed improving different instruments in order to favour the relocation of the surplus of labour.
Keywords: Delocalization; Offshoring; Foreign direct investment; Semi-manufactured goods imports